Kajian Teknik Aplikasi Drainase Bawah Tanah dengan Menggunakan Bahan Baku Lokal - Imanudin, Momon Sodik (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2016)
Problems crop cultivation on rain fed land after rice is still too wet for crops, while for rice crop will experience drought on the generative phase. The technology was required to decrease the moisture content of the soil so that crops can be planted after rice. The study aims to examine the application of the use of the underground drainage system to lower the water logging. Local raw materials were used in order to easily adopted by farmers, because common uses of the pipe is still too expensive. The drainage material was made of a collection of coconut husk and wood twigs. As a test medium performed using texture medium sandy clay loam soil and sand. The test results showed that the ability of the drainage flow on coconut fiber, lower than that of wood sticks consecutive 0.37 and 0.48 liters / sec. And the maximum flow capability was shown in the sandy soil of 0.75 and 1.93 liters / sec. Condition of the land with drainage modulus 10mm / day and the structure of materials was used in the field of wood sticks with inter-channel spacing is 10 m, then there is a 10 in 1 ha pipeline, so the ability to discharge to 69 m3 / h. Therefore, it took time for water discharge at 100/69 = 1.45 This means that the potential of using systematically drainage disposal is fit for use primarily in the light texture such as sandy clay loam.